Beyond the target insects: impacts of Bti on aquatic macrofauna communities - Julia C. van Nieuwpoort; Maarten Schrama; Jeroen Spitzen; Sam Philip Boerlijst (Parasites & Vectors)
Abstract Background The larvicide Bacillus thuringiensis israelensis (Bti) was introduced as a pest control method in the 1980s, claiming not only to be effective, but also to target specific insect groups including Culicidae and Simulidae, with no substantial effects on non-target species or to the local ecosystem. Methods To test these claims, we applied Bti to a naturally colonized, replicated set of aquatic macrocosms under realistic, field-like conditions, and investigated impacts on non-target species, including effects on related taxa and higher trophic levels. Results Our results indicate limited effects on most invertebrate prey taxa, with the exception of a decimation of the Chironomidae, which compose up to 50% of the biomass of these aquatic ecosystems. Effects on invertebrate predators including Hemiptera, Odonata and Coleoptera were investigated but were only observed for 1 species of Odonata: a small but significantly negative effect on larvae of Ishnura elegans (Odonata: Zygoptera). Conclusions Overall, our results support the claim that, when used during short intervals at small spatial extents, Bti has limited effects on aquatic ecosystems, and that effects are relatively short-lived. However, negative effects on Chironomidae and Odonata larvae warrant careful use of the substance at natural water ecosystems, especially as the former insect family constitutes the basis of the aquatic food in soft-sediment freshwater aquatic systems and Bti leads to a local temporary near-complete wipeout of this Diptera family. Overall, our results highlight the need to define and limit the spatial and adhere to the advised temporal extent at which Bti is used. Graphical Abstract